Why does headquaters voluntarily transfer its bargaining power to business units? / Shin'ya Okuda, Takaya Kubota and Yoshimi Chujo. - Okuda, Shin'ya; Kubota, Takaya; Chujo, Yoshimi (Universiti Teknologi MARA, Shah Alam, 2019)
The objective of our paper is to provide the reason why the headquarters voluntarily transfer its bargaining power to the business unit by stylizing an incomplete contract model. Our model shows that the equilibrium bargaining power selected by the headquarters is negatively correlated with the importance attached to the business unit’s operations. It means when incomplete contracts severely restrict an important business unit’s incentive to invest because of holdup problem, then the headquarters should necessarily provide the business unit with some degree of bargaining power. This result is consistent with the fact that the independence of a business unit (e.g., spin-offs) is a commonly observable practice. Building on our model, independence of the business unit can be interpreted as a consequence of a gradual delegation of authority by the headquarters. Our paper contributes to both of economics and management accounting literature through providing a model concerning to a decision of organizational structure.